Optimization of Electrical Conductivity of SA-graphene Nanocomposites Using Response Surface Methodology - Sahal, Hakan; Torgut, Gulben; Canpolat, Erdal (Higher Education Press, 2022)
Synthesis and characterization of 4-{(E)-[(5-bromo-2-hydroxyphenyl)methylidene]amino}-N-carbamimidoylbenzene-1-sulfonamide(SA) and its composites with graphene(SA-GF) were performed. Compound SA and SA-GF were characterized by FTIR and H-1 NMR. The GF dispersion in the composites was analyzed by means of scanning electron microscopy(SEM) for morphology. Thermal properties of SA and nanocomposites were investigated using differential thermal analysis(DTA) and thermogravimetric analysis(TGA). The optimum electrical conductivity of the new sulfonamide-based Schiff base was determined to be 1.78x10(-5) S/cm at a frequency of 9923 Hz, an applied voltage of -19 V, a mass fraction of 9.38% for graphene loading using a central composite design in the response surface methodology. The significance of the selected parameters(frequency, voltage and GF amount) in the model was determined by the analysis of variance(ANOVA). The results showed that frequency and graphene loading represent important model terms and have considerable effects on the conductivity of SA.
Keywords: Schiff base; Sulfonamide; Graphene; Conductivity; Nanocomposite